The Construction of Mathematical Model for the Mechanism of Protein Synthesis Involving mTORC1 from the AMPK Pathway - Ari Kusumastuti; Mohammad Jamhuri; Dewi Firdaus; Nurul Anggraeni Hidayati ((IJCSAM) International Journal of Computing Science and Applied Mathematics, 2023)
This study discusses the construction of mathematical models for the mechanism of protein synthesis involving the main regulator mTORC1 gene which is described in the singular pathway mTOR of the AMPK pathway. The genes in question include: AMPK, TSC2, Rheb, mTORC1 and S6K. The method used for this research is divided into two stages, namely pathway analysis for the mechanism of protein synthesis and the second is the formulation of mathematical models. Pathway analysis is performed as a reference in describing interactions in the form of kinetic reaction schemes. After the interaction scheme is created, it is then formulated into a mathematical model with the independent variable being time. Mathematical models for the mechanism of protein synthesis involving mTORC1 of the AMPK pathway in the form of ordinary time-dependent differential equations involving independent variables [TSC2], [pAMPK], [pTSC2], [Rheb^{GTP}], [Rheb^{GDP}], [mTORC1], [Raptor], [aRaptor], [Deptor], [PRAS40], [mTOR], [amTORC1], [mLST8], [S6K1] and [pS6K1].